Analysis of the disease burden of cardiomyopathy in children aged 0–14 years in China from 1990 to 2019 - Kong, Qingyu; Li, Meng; Wang, Minmin; Zhao, Haizhao; Yang, Xiaorong; Zhao, Cuifen (Frontiers in Public Health, 2023)
Objective To assess the disease burden and changing trend of cardiomyopathy in children aged 0-14 years in China from 1990 to 2019.This study was based on the Global Burden of Disease Study 2019; the age-specific prevalence rate, mortality rate and disability-adjusted life year (DALY) rate were used for analysis. Estimated annual percentage change (EAPC) in burden rate and its 95% confidence interval were calculated. The data of China were compared with the global average level.In 2019, the numbers of prevalence, deaths, and DALYs of cardiomyopathy in children aged 0-14 years in China were 4493 [95% uncertainty interval (UI): 2687 6838], 434 (95%UI: 337 565) and 37522(95%UI: 29321 48891), with declining amplitudes of 16.32%, 70.56%, and 70.74%, compared with 1990 respectively. In 2019, the prevalence rate of cardiomyopathy in Chinese children aged 0-14 years was 2.00/100,000 (95%UI: 1.2/100,000 3.04/100,000), higher than 1990 [1.66/100,000 (95%UI:1.00/100,000 2.53/100,000)]; mortality rate was 0.19/100,000 (95%UI: 0.15/100,000 0.25/100,000), significantly lower than 1990 [0.46/100,000 (95%UI: 0.25/100,000 0.95/100,000)]; DALY rate was 16.69/100,000 (95%UI: 13.04/100,000 21.75/100,000), also significantly lower than 1990 [39.71/100,000 (95%UI: 22.06/100,000 82.8/100,000)]. All burden rates of cardiomyopathy in Chinese children aged 0-14 years old were all lower than the global averages of 2019; the burden rates of male children were higher than female children. In all calendar years from 1990 to 2019, the mortality and DALY rates of children younger than 1-year-old were significantly higher than in the other age groups of 0-14 years old.From 1990 to 2019, the prevalence rate of cardiomyopathy aged 0-14 years old gradually increased, with EAPC of 0.82 (95%CI: 0.71 to 0.93); mortality rate and DALY rate decreased [EAPC= -2.32 (95%CI: -2.59 to -2.05)].Conclusions From 1990 to 2019, the disease burden of cardiomyopathy in children of China aged 0-14 years was heterogeneous; the burden of male children was higher than females; and the burden of cardiomyopathy in children younger than 1 year old needs more attention.